Development of a New Method for Determination of Lead in Urine by Anodic Stripping Pulse Voltammetry in Methanol - Ramadan, A.A.; Mandil, H.; Asaad, W. (Asian Journal of Chemistry, 2010)
A sensitive and selective anodic stripping pulse voltammetric method in methanol containing 0.1M HCl as supporting electrolyte at RDGCE was employed to determine traces of lead. The linear ranges were obtained at the concentration ranges of 6x10-8 to 2x10-6 M with 60 s deposition time and 50 mV amplitude pulse, 4x10-8 to 1x10-6 M with 60 s deposition time and 100 mV amplitude pulse and 4x10-9 to 9x10-8 M with 200 s deposition time and 100 mV amplitude pulse. The detection limit was 4x10-9 M with relative standard deviation equal to ± 5.1%. Most of the metal ions do not interfere during the determination. The developed method was applied to lead determination in urine. The concentrations of lead in the urine samples ± SD, ranged from 248.40 ± 3.35 μg/L to 1045.33 ± 22.33 μg/L, while the urine lead materials show more troublesome particles at concentrations above 600 μg/L.